In vitro antimicrobial studies of new Zn (II) complexes of N- hydroxymethylsaccharin (Sac-CH2OH) and amine ligands - Al-Janabi, Ahmed S. M. (Journal of Kerbala for Agricultural Sciences, 2017)
A new five Zn(II) complexes of the type [Zn(Sac-CH2O)2(NÙN)] where NÙN = Bipy, Phen, en, dmen were prepared from the reaction of diamine ligands NÙN with [Zn(Sac-CH2O)2] in equivalent molar ratio. The prepared complexes have been characterized by IR, 1HNMR, elemental analysis, and molar conductivity. The antimicrobial studies of the Zn(II) complexes were also tested against Escherichia coli, and Pseudomonas aeruginosa, as Gram-negative; Staphylococcus aureus, Salmonella typhi, and Bacillus subtilis, as Gram-positive bacteria . and results suggested that Zn(II) complexes have significant antimicrobial activity.